2007
DOI: 10.1007/s10457-007-9061-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient use efficiency and biomass production of tree species for rotational woodlot systems in semi-arid Morogoro, Tanzania

Abstract: Frequent nutrient removals accompanying wood and crop harvests from rotational woodlot systems may contribute to declining site productivity and sustainability because of soil nutrient depletion. However, selecting for nutrient-efficient tree species may well sustain productivity under this system. To test this hypothesis, a randomized complete block experiment was adopted to assess effects of five tree species on soil nutrients status, nutrient use efficiency and wood yield in semi-arid Tanzania. After 5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 16 publications
1
27
1
Order By: Relevance
“…The effects of Acacia plantations on soils have been investigated in many studies, especially recently. Some studies have reported positive effects on topsoil of N accumulation (Fisher 1995;BernhardReversat 1996;Majalap 1999;Garay et al 2004;Jang et al 2004;Xue et al 2005;Kimaro et al 2007;Macedo et al 2008;Kunhamu et al 2009) and/or N mineralization (Majalap 1999Li et al 2001;Kimaro et al 2007). Vitousek et al (2002) pointed out the importance of N 2 fixation as a source of N cycling in tropical ecosystems, and a large organic N flux through litterfall is likely to enhance N availability in tropical forest plantations.…”
Section: Effect Of Element Flux In Litterfall On Soil Chemistrymentioning
confidence: 95%
See 1 more Smart Citation
“…The effects of Acacia plantations on soils have been investigated in many studies, especially recently. Some studies have reported positive effects on topsoil of N accumulation (Fisher 1995;BernhardReversat 1996;Majalap 1999;Garay et al 2004;Jang et al 2004;Xue et al 2005;Kimaro et al 2007;Macedo et al 2008;Kunhamu et al 2009) and/or N mineralization (Majalap 1999Li et al 2001;Kimaro et al 2007). Vitousek et al (2002) pointed out the importance of N 2 fixation as a source of N cycling in tropical ecosystems, and a large organic N flux through litterfall is likely to enhance N availability in tropical forest plantations.…”
Section: Effect Of Element Flux In Litterfall On Soil Chemistrymentioning
confidence: 95%
“…Understanding of the effect of N 2 -fixing trees, particularly A. mangium, on soil conditions has recently improved (Fisher 1995;Bernhard-Reversat 1996;Majalap 1999;Li et al 2001;Garay et al 2004;Jang et al 2004;Xue et al 2005;Kimaro et al 2007;Abdu et al 2008;Macedo et al 2008;Yamashita et al 2008;Kunhamu et al 2009). Some studies have found more organic matter and N accumulation in soils of A. mangium stands than in those of non-legume tree stands.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, such efficient P cycling likely occurs at a field level and such differences in N and P cycling may be reflected in N:P ratios. We anticipated that plantation forests would exhibit different N:P ratios for each planted species as has been shown in natural tropical forests (Townsend et al 2007) because nutrient demands or N-and P-use efficiency differ among species (Kimaro et al 2007;). Litterfall of N 2 -fixers is expected to have higher N:P ratios; e.g.…”
Section: Introductionmentioning
confidence: 98%
“…The same study reported fuelwood production amounts of 1 MT ha ֿ◌¹ after a 2 year Gliricida/maize intercrop and 3.3 and 5.0 MT ha ֿ◌¹ after 3 years of Gliricida/maize/pigeon pea and Gliricidia/maize intercrop, respectively (Chirwa et al, 2003). A 5 year Gliricidia rotational woodlot in Tanzania was found to produce over 30 MT of woody biomass (Kimaro et al, 2007). Faidherbia albida and Leucaena leucocephala are two other SFR species planted in the southern Africa region that are managed for the dual purpose of soil fertility and woody biomass production (AFT, 2008).…”
Section: Wood Production For Construction and Energymentioning
confidence: 88%